Synchronization and Coordination of Art Performances in Highly Competitive Contexts: Battle Scenes of Expert Breakdancers - Shimizu, Daichi; Okada, Takeshi (Frontiers in Psychology, 2021)
In the performing arts, such as music and dance performance, people actively interact with each other and show their exciting performances. Some studies have proposed that this interaction is a social origin of the performing arts; some have further investigated this phenomenon based on the theory of synchronization and coordination. Though the majority of these studies have focused on the collaborative context, several genres of the performing arts, such as jazz sessions and breakdance battles, have a competitive context. Several studies have suggested that, in this competitive context, performers actively interact with each other and construct some correspondence. Moreover, a few recent studies focusing on competitive conversations, such as debates, have shown that, compared to people’s interactions in collaborative conversations, people in competitive contexts frequently coordinate their behaviors in complicated ways. However, the interaction and coordination among performers in these competitive contexts have not been sufficiently investigated. Therefore, we investigated the coordination of expert breakdancers in battle scenes and measured their rhythmic movements using a motion capture system. We calculated the relative phase of the rhythmic movements between two dancers to investigate their coordination. The results showed that the dancers’ rhythmic movements tended to synchronize in an anti-phase fashion, which means that there were similarities as well as differences between the two dancers’ rhythmic movements. Further, this pattern of synchronization changed dynamically as time elapsed, from in-phase synchronization to anti-phase synchronization and then to no apparent synchronization.